Cross-sectional associations between Ideal Cardiovascular Health scores and vascular phenotypes in 11- to 12-year-olds and their parents: The Longitudinal Study of Australian Children - Ranganathan, Sarath; Azzopardi, Peter; Cheung, Michael; Edwards, Ben; Juonala, Markus; Dwyer, Terence; Grobler, Anneke; Lycett, Kate; Wake, Melissa; Burgner, David; Liu, Richard (My University, 2019)
Background: Understanding early-life relationships between the Ideal Cardiovascular Health (ICVH) score and vascular phenotypes could inform likely effectiveness and timing of cardiovascular disease prevention strategies. We aimed to describe associations between ICVH scores and vascular phenotypes in 11- to 12-year-old children and their parents. Methods and results: Cross-sectional ICVH scores (range 0–7, higher indicating better health), derived by summing dichotomized metrics for cholesterol, glucose, blood pressure (BP), body mass index (BMI), diet, physical activity and smoking, were constructed for 1235 adults (89% female, mean age 43 years) and 1028 children (48% female, 12 years). The median scores were 4 and 5 for adults and children respectively. Child ICVH scores were associated with parent scores (0.18 higher child score per additional point in parent's score, 95% CI 0.12 to 0.22, P b 0.001). Each additional point in the adult ICVH score was associated with slower carotid-femoral pulse wave velocity (PWV, −0.32 m/s, 95% CI −0.37 to −0.27), greater carotid elasticity (0.017%/mm Hg, 95% CI 0.014 to 0.020) and reduced carotid intima-media thickness (IMT, −7.3 μm, 95% CI −12.0 to −2.5). An additional point in the child score was associated with functional phenotypes (PWV −0.07 m/s, 95% CI −0.11 to −0.03; carotid elasticity 0.009%/mm Hg, 95% CI 0.004 to 0.015) but not structural phenotypes (IMT −1.8 μm, 95% CI −5.2 to 1.5). Conclusion: Few Australian children and even fewer parents have ideal cardiovascular health. Lower ICVH scores were associated with adverse adult vascular phenotypes and adverse child vascular function. Family-based interventions optimizing ICVH metrics may delay onset and progression of subclinical atherosclerosis and later cardiovascular disease.
International Journal of Cardiology
Keywords: Children; Health -- Physical; Health and wellbeing; Children; Health; Physical; Health and wellbeing